Fitness of ALS-Inhibitors Herbicide Resistant Population of Loose Silky Bentgrass (Apera spica-venti) - Babineau, Marielle; Mathiassen, Solvejg K.; Kristensen, Michael; Kudsk, Per (Frontiers in Plant Science, 2017)
Herbicide resistance is an example of plant evolution caused by an increased reliance on herbicides with few sites of action (SoA) to manage weed populations. This micro-evolutionary process depends on fitness, therefore the assessment of fitness differences between susceptible and resistant populations are pivotal to establish management strategies. Loose silky bentgrass (Apera spica-venti) is a serious weed in Eastern, Northern and Central Europe with an increasing number of herbicide resistant populations. This study examined the fitness and growth characteristics of an ALS resistant biotype. Fitness and growth characteristics were estimated by comparing seed germination, biomass, seed yield and time to key growth stages at four crop densities of winter wheat (0, 48, 96 and 192 plants m-2) in a target-neighbourhood design. The resistant population germinated 9 to 20 growing degree days (GDD) earlier than the susceptible population at 10, 16 and 22°C. No differences were observed between resistant and susceptible populations in tiller number, biomass, time to stem elongation, time to first visible inflorescence and seed production. The resistant population reached the inflorescence emergence and flowering stages in less time by 383 and 196 GDD, respectively, at a crop density of 96 winter wheat plants m-2 with no differences registered at other densities. This study did not observe a fitness cost to herbicide resistance, as often hypothesized. Inversely, a correlation between non-target site resistance (NTSR), earlier germination and earlier flowering time which could be interpreted as fitness benefits as these plant characteristics could be exploited by modifying the timing and site of action of herbicide application to better control ALS NTSR populations of A. spica-venti.